The nanotech: you index innovative for the society, the economy and their regulation - Armas Morales, Carlos Eduardo (2015)
The present article becomes of an exploratory investigation whose initial purpose the knowledge of the nanotech was centered in the university community (UNMSM and other), that which allowed to document us in the impacts of the nanotech in some aspects of the society (thinking of the Peruvian society) taking like reference the health and the feeding; as well as the innovations that it would happen in the production, circulation and commercialization of products with technology. Also the changes that would be gestated for the regulation of the nanotech to avoid excesses that could have their use, commercialization and application, among others that he/she brings get this technology.